2021
DOI: 10.1111/jen.12882
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐mediated effects on life history traits of entomovirus infected caterpillars ofSpodoptera exigua

Abstract: It has been reported that host plants are able to mediate the interactions between insect herbivores and entomoviruses, but how plants affect growth, development, detoxifying enzymes and metabolic enzymes of herbivores infected by entomoviruses has only rarely been studied so far. We compared growth, development duration, activity of a detoxifying enzyme (carboxylesterase) and a metabolic enzyme (acetylcholinesterase) of a caterpillar (Spodoptera exigua) infected with an entomovirus (SeMNPV) or left non‐infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The findings inform host plant decision-making, particularly in the view of massproducing SfMNPV using natural media. They also corroborate insect melanization-related enzyme activity associated with diets with low viral loads, as demonstrated in earlier works [42,43]. In addition, both Cisneros et al and Gómez et al [28,44] reported that improved formulations of SfMNPV with maize flour and 1% boric acid and microencapsulation are effective for the control of FAW.…”
Section: Discussionsupporting
confidence: 82%
“…The findings inform host plant decision-making, particularly in the view of massproducing SfMNPV using natural media. They also corroborate insect melanization-related enzyme activity associated with diets with low viral loads, as demonstrated in earlier works [42,43]. In addition, both Cisneros et al and Gómez et al [28,44] reported that improved formulations of SfMNPV with maize flour and 1% boric acid and microencapsulation are effective for the control of FAW.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are consistent with some earlier reports, which have shown a significant decrease in pupal weight in A. gemmatalis and S. frugiperda and a significant prolongation of larval developmental periods in S. frugiperda with increasing rutin concentration in the diet (Hoffmann‐Campo et al 2006; Silva et al 2016). Moreover, as a flavonoid compound, rutin had similar functions to other flavonoids, such as quercetin, which significantly inhibited pupal weight and led to considerably longer larval developmental durations in beet armyworms (Fan et al 2022). However, there was no change in the 7‐day mortality of pink bollworm larvae fed a diet incorporated with rutin (Table 1), which differed from previous reports that rutin caused a significant increase in larval mortality in S. litura at 7 days after treatment and in Helicoverpa armigera at 5 days after treatment (Su et al 2018; Zhang et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Plant-mediated effects on the susceptibility of insect herbivores to entomoviruses play an important role in understanding the tritrophic interactions of plants, herbivores and entomoviruses (Cory and Hoover 2006;De Roode et al ., 2010;Wan et al , 2016;Elderd et al ., 2013). The differences in such susceptibility can be accounted for not only by differences in insect growth and movement behavior (Wang et al ., 2021a;Sarfrazet al ., 2011), but also by immune responses of herbivores to entomoviruses (Shapiro et al ., 2009;Wang et al ., 2020Wang et al ., , 2021b. Additionally, such virus susceptibility differences can be reflected by plantmediated alteration of insect guts (especially peritrophic membranes, PMs) and entomovirus infection via plant trichome structure.…”
Section: Introductionmentioning
confidence: 99%